Silica deposits on Mars with features resembling hot spring biosignatures at El Tatio in Chile - Steven W. Ruff (Nature Portfolio, 2016)
Hydrothermal deposits on Mars may provide the best opportunity to find Martian biosignatures. Ruff and Farmer report that silica structures created by biotic and abiotic process in hot springs at El Tatio, Chile resemble those found in Gusev crater, thus making it an ideal location for future missions.